Maintenance of richness despite reduced abundance of desert bees (Hymenoptera: Apiformes) to persistent grazing. Issue 3 (27th July 2013) - Minckley, Robert L.; Stewart, Alan; Packer, Laurence
Abstract Anthropogenic changes to ecosystems typically result in decreased species richness and abundance relative to that of adjacent semi‐pristine or pristine areas. Yet, there is debate about the generality of this result for bees given that most studies have included extremely disturbed areas and are from a limited set of biogeographical areas. Repeat sampling of an unusually specialised, species‐rich bee community was done in the north‐western Chihuahuan Desert, North America at sites in five habitats (riparian, mesquite forest, abandoned field, grassland, and desert scrub) that either had been intensely grazed by cattle in the previous year or not been grazed for 22+ years. Species density and species composition of bees did not change in response to grazing, abundance and proportion of singleton species (those represented by one specimen) did. In all habitats, other than the riparian, there was lower overall abundance and a greater proportion of singleton species at sites that had been recently grazed than at sites that had not been grazed since 1979. The proportion of singletons was greater in recently grazed than in long‐term ungrazed areas, but pollen‐specialist species did not respond more strongly than pollen generalists. The substantial variation in bee abundance and rarity was probably associated with differences in floral resources. Overall, lower bee abundance in grazed areas reflects the continuous removal by grazers of the flowers that bees use. Despite reduced bee abundance due to long‐term grazing, species richness, and composition in this desert bee community remained high.